2019
DOI: 10.1136/bmjopen-2018-025789
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of elderly patients regarding participation in their hospital discharge: a qualitative metasummary

Abstract: BackgroundAgeing patients are discharged from the hospital ‘quicker and sicker’ than before, and hospital discharge is a critical step in patient care. Older patients form a particularly vulnerable group due to multimorbidity and frailty. Patient participation in healthcare is influenced by government policy and an important part of quality improvement of care. There is need for greater insights into the complexity of patient participation for older patients in discharge processes based on aggregated knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
60
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 65 publications
7
60
0
12
Order By: Relevance
“…One important aspect of improving the transitional care experience is to make transitional care more patient-centered. Previous research on patient involvement in transitional care has revealed that older patients experience a lack of participation during transitions [8][9][10][11]. Transitional care is also characterized by the challenges of coordinating care across organizational and disciplinary boundaries, managing conflicting goals of care, which may be stressful for health care providers (HCPs) [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…One important aspect of improving the transitional care experience is to make transitional care more patient-centered. Previous research on patient involvement in transitional care has revealed that older patients experience a lack of participation during transitions [8][9][10][11]. Transitional care is also characterized by the challenges of coordinating care across organizational and disciplinary boundaries, managing conflicting goals of care, which may be stressful for health care providers (HCPs) [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…As the average length of stay declines, older people are being discharged from the hospital "quicker and sicker" than before (Deniger et al, 2015;Galvin et al, 2017;Spehar et al, 2005). Although there has been increasing studies in the area care transitions for older patients and how this situation affects the patient and their informal caregiver (Gupta et al, 2019;Hvalvik & Reierson, 2015;Jeffs et al, 2017;Lilleheie et al, 2020Lilleheie et al, , 2019, there are few studies addressing how this influences feelings of reciprocity, equity and family dynamics. Furthermore, few studies have focused on the experience of caregiver burden and on recipients' feelings of being a burden (Sales, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Studies and reports have highlighted that service users who are actively engaged in their health and care can experience better health outcomes and care experiences (7,34,42). However, research shows that, in many situations, user involvement is too little integrated into health care for elderly (35,43). There are several studies from hospitals and discharge processes to home care or mental health, but few empirical studies on user involvement are from public home care services (35,(43)(44)(45).…”
Section: User Involvementmentioning
confidence: 99%
“…The study by Bjørkquist et al (6) indicates that involving elderly service users in the process of implementing welfare technology is challenging due to a lack of competence and information about what technology is available and what service users might bene t from. Another study found that elderly service users reported that they often struggled to understand and remember the information they were given about welfare technology, which is a challenge for user involvement (43). Bennett (20) argues that consideration must be given to patients' decision-making capability and human rights in connection with user involvement.…”
Section: User Involvementmentioning
confidence: 99%